Ein „politisch schiefer Kopf“ und der „letzte Mumienkasten“ - Humboldt und Metternich - Biermann, Kurt-R. (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2004)
Abstract In this short essay, the Alexander von Humboldt scholar Kurt-R. Biermann (1919-2002) shed some light on the relationship between the famous conservative Austrian statesman Prince Metternich and the liberal Prussian scientist Alexander von Humboldt. It is one of the old legends that Humboldt and Metternich had studied together in Göttingen. They first met 1807 in Paris and corresponded in the most polite manner basically on one common field of interest, namely the promotion of the sciences.